ANALYSIS OF PROJECT DELAY USING THE CRITICAL PATH METHOD (CPM): A CASE STUDY ON THE CONSTRUCTION PROJECT OF THE OPD OFFICE BUILDING IN PASURUAN - Purnomo, Didik; Oetomo, Wateno; Marleno, Risma (Transpublika Publisher, 2024)
In construction project control, the main factors of concern are quality, time and cost control. So it is necessary to use one method in the implementation of control. This study aims to analyze the time and cost of the Raci OPD Office Building Construction project. The benefit of this research is to anticipate potential delays that occur in the project. The problem limitation is focused on work that has not been completed in the remaining time of the contract period. To analyze time and cost, this research uses Critical Path Method (CPM) and Time-Cost Trade-Off (TCTO) which begins with determining the work network and critical path. TCTO analysis is carried out by shortening the duration of work by adding 3 hours of overtime and calculating the Crash Slope of each job on the critical path. Rescheduling is done by accelerating the work that has the lowest cost. The results showed that the most effective rescheduling was carried out on the Lt.3 Installation and Plastering work with the acquisition of an acceleration duration of 8 days. And the total cost required for this acceleration is Rp. 29,441,424, - or Rp. 1,226,726, - per day for 24 days.